Investigating English Language Teachers’ TPACK Competencies on the Students’ Writing Skill - Rahma Ayuditya Putri (CV. Akademi Merdeka, 2025)
This study aims to explore English teachers' implementation of Technological Pedagogical Content Knowledge (TPACK) competencies to enhance students' writing skills. The methods used include qualitative observations and interviews, focusing on the use of technology in writing instruction, variations in TPACK implementation, impact on student engagement, and teachers' perceptions of their TPACK competencies. The findings of this study are expected to provide valuable insights for effective pedagogical practices and professional development for teachers.